Effects of cooling rate on the mechanical properties and precipitation behavior of carbides in H13 steel during quenching process. (30th December 2020) - Ning, Angang; Gao, Rui; Yue, Stephen; Guo, Hanjie; Li, Lingxia
Abstract: The effects of cooling rate (CR) on the mechanical properties and precipitation behavior of carbides in H13 steel during quenching process were investigated. The retained austenite tends to be more unstable with increasing CRs, while the martensite increases gradually, based on XRD analyses and EBSD results. The values of hardness are increased, and the elongation along with impact energy is decreased, respectively, at higher CRs. Tensile strength remains above 2.0 GPa. Work hardening rates increase considerably in three samples, suggesting that transformation-induced plasticity effect may take place during the tensile test. Moreover, an increase in yield strength is observed when CR exceeds 15 K s −1, possibly due to a high volume fraction of martensite, decline in average grain size and precipitation of fine carbides. Types of the precipitates acquired were identified by electrolysis and XRD analyses. The results indicate the predominant existence of MC, M6 C and M7 C3, which are confirmed by SEM-EDS analyses and FactSage thermodynamic calculations. The size, volume and distribution of the carbides were also scrutinized under SEM. It is found that the volume fraction and size of the precipitates both decrease with increasing CRs. Based on these experimental data, an optimum CR for the quenching process could be determined to achieve the desired distribution of carbides, which in turn leads to the enhanced mechanical behaviors.